A bridge too far: cold and pathogen constraints to assisted migration of riparian forests. Issue 6 (3rd July 2015) - Grady, Kevin C.; Kolb, Thomas E.; Ikeda, Dana H.; Whitham, Thomas G.
Abstract : Assisted migration of warm‐adapted genotypes to currently cooler climates may reduce maladaptation from future climate change. Few assisted migration trials have considered limitations of the cooler climates and pathogens currently present at transplant sites. This is especially important to consider in riparian ecosystems that are priority targets for restoration in the western United States as they harbor diverse communities. In an effort to validate assisted migration as an effective strategy for mediating the negative impacts of climate change, we used a provenance trial with replicated genotypes from 19 populations of the foundation riparian tree species, Fremont cottonwood ( Populus fremontii ), transplanted to a cold site to test for genetic variation in growth, mortality, and resistance to shoot blight fungi ( Venturia sp.). Populations from cool sites had up to 4 times faster growth, 3 times higher survival, and 8 times higher resistance to Venturia than populations from warm sites, providing evidence of local adaptation to both climate and pathogenic fungi. Budburst phenology and shoot blight were correlated with frost damage, subsequent shrub‐form architecture, and mortality. While climate change models predict 6°C increases, plants transferred distances of 6°C at this time would not perform well; an intermediate transfer distance of less than 3°C would avoid maladaptation to the current environment during assisted migration. Thus, multiple and intermediate transfer phases to supplement local genetic variation will likely be necessary for effective assisted migration to accommodate current environments and large changes in climate.